Vernaculars in an Age of World Literatures - Kullberg, Christina; Watson, David (Cosmopolitan-Vernacular Dynamics in World Literatures, 2022)
This open access book complicates and develops the notion of the vernacular. Understood in the linguistic sense as well as an element of the local, the vernacular facilitates the exploration of local and global dynamics. Through exploring the unexamined active role of the local, the indigenous, and the periphery in international literary exchanges, this volume argues that a coherent theorization of the vernacular will enable us to do so. The essays in Vernaculars in an Age of World Literatures present new critical approaches in the debate on world literature, which has given priority to cosmopolitan movements, global circulation of literatures, and metropolitan centers. In nine case studies, approaching narratives from the long 20th century from more or less marginal contexts-such as the Francophone Chinese diaspora, multilingual regions in Spain, West Africa, and the Caribbean-the volume offers theoretical and methodological ways of putting the concept of the vernacular in practice and demonstrates how vernaculars operate within different literary, critical, cultural, and political circumstances. The open access edition of this book is available under a CC BY-NC-ND 3.0 licence on www.bloomsburycollections.com. Open access was funded by Riksbankens Jubileumsfond.